Probability of Electron Ion 3Li^(2+) In Momentum Space At n â‰¤ 3 - Safina Aulia Sani; Rike Dwi Wulandari; Ana Zuyyina Ulfah; Bambang Supriadi; Nilam Cahya Kusumaningtyas (Postgraduate, University of Mataram, 2023)
Lithium ions (3)Â is a particle that has a single electron and is formed because lithium metal loses 2 of its 3 valence electrons. Probability is the square modulus of a wave function. Electron probability is a description of the discovery of electrons in space. This study aims to determine the probability value of electron momentum of Lithium ion (3). This type of research is non-experimental research in the form of developing existing theories with theoretical research methods. When viewed from the main orbital quantum value, the greater the probability value or the easier the electron is found at a larger quantum number. When viewed from the level of the probability interval, the greater the probability interval, the greater the main quantum value. In accordance with the theory which states that the large main quantum number n and orbital quantum l result in the probability value of Lithium ions getting bigger.